The Effect of Some Nanoparticles on The Growth of Multi-Resistant Escherichia Coli Bacteria Isolated From Different Sources in Diyala University: Pengaruh Beberapa Nanopartikel Terhadap Pertumbuhan Bakteri Escherichia Coli Multi Resisten yang Diisolasi dari Sumber yang Berbeda di Universitas Diyala - Al-Dulaimi, Ibrahim. M.; Nuaimi , Ahmed .I. Al; hasan, Mohammed .A. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Escherichia coli bacteria possess a number of virulence factors, in addition to their ability to acquire enterotoxin genes through plasmids or bacteriophages, or through genes acquired from other pathogenic bacterial genera through bacterial conjugation. The resistance to antibiotics that bacteria possess is considered one of the most important economic and health problems around the world. Nanoparticles are mainly used in antibacterial applications due to their long-term stability and biocompatibility. The mechanisms behind the antimicrobial effect of these nanoparticles are metal ion release, oxidative stress, and non-oxidative stress that occur simultaneously. Mineral nanoparticles are characterized by their broad-spectrum properties against both Gram-negative and Gram positive bacteria. Objectives: The study aimed to determine the effect of nanomaterials on the growth of E. coli bacteria Methods: Been collected of 100 samples collected from urinary tract infections and stool in Sterile bottles in different hospitals in Baquba city (Baquba Teaching Hospital and Al- Batool Hospital) It was subjected to detecting the resistance of the isolates to six antibiotics and the extent of the effect of nanomaterials on bacterial growth Results: Thirty-three isolates of E. coli bacteria were obtained. From urine and stool, the isolates were tested for resistance to six antibiotics: Amoxicillin-Clavulanic acid, Cefotaxime, Cefepime, Ciprofloxacin, Ampicillin, and Tetracycline. The effect of nanomaterials, silver and zinc nanoparticles, on bacterial growth was determined, as the results showed a decrease in bacterial growth as a result of the use of nanomaterials. Conclusion: Escherichia coli isolates are characterized by their multiple resistance to antibiotics, which increases their pathogenicity. The use of nanoparticle inhibitors of silver and zinc led to a decrease in bacterial growth, which makes them used as alternatives in treatment. Highlights: coli shows virulence, gene transfer, and antibiotic resistance. Evaluate nanomaterials' effect on E. coli bacterial growth. Silver, zinc nanoparticles reduce E. coli growth; potential antibiotic alternatives. Keywords: Escherichia coli. Nanoparticles; urinary tract infection; Antibiotic resistance